A collaborative approach to improving patient access in general practice: impact of three different pilot schemes in 12 general practices in Greenwich. Issue 4 (3rd July 2016) - Lawless, Melanie; Wright, Ellen; Davidson, Jackie
Abstract: Background: With rising patient demand and expectations, many practices are struggling to respond to the demand for appointments. Objective: To investigate different approaches to improving access to general practice and assess the impact on (i) patient experience, (ii) practice staff experience and (iii) activity in A&E and walk-in centres. Method: Greenwich CCG piloted three approaches in 12 volunteer practices. The schemes were: (1) Systematic GP telephone triage of all appointment requests. (2) Analysis and comparison of practice data including demand and capacity to identify opportunities for improvement. (3) Online consultations. Qualitative and quantitative evaluation was undertaken. Results: Overall results were inconclusive and no one pilot scheme was overwhelmingly successful in improving patient experience of access or reducing practice workload. Scheme 1 telephone triage: In some cases, overall demand on clinician time through the day reduced as face-to-face consultations were replaced with shorter telephone consultations. However, in other practices, total consulting time went up when telephone consultations took longer than the suggested average 5 min. Scheme 2 practice analysis and benchmarking: The pilot practices implemented no significant changes. Scheme 3 online consultations: Take up was low, with users as a percentage of total list size dropping significantly to even lower levels in the second half of the pilot – from 3.13% in the first three months to 1.20% in the second three months. Conclusion: As the pilots did not improve the overall patient experience of access or practice workload, the pilot schemes were not rolled out by the CCG. From the CCG's point of view, it was valuable to test out the effect of a scheme before committing further resources.